PMIA / F127 / TA porous membrane and preparation method thereof
By introducing Pluronic F127 and TA into the PMIA polymer film, and using the NIPS method and the forced surface segregation process, PMIA/F127/TA porous membrane with high permeability and selectivity was prepared, solving the problem of membrane performance optimization in the prior art.
Patent Information
- Application Number
- CN202411912014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
It is difficult to prepare high-porosity PMIA polymer films with high permeability and selectivity, and methods to improve the porosity and pore size of the membrane surface often affect other properties of the membrane.
The preparation method of PMIA/F127/TA porous membrane was adopted, and the NIPS method and the forced surface segregation process were used to form a film with a uniform, smooth and porous structure, thereby improving the porosity and permeability of the membrane.
The permeability flux and selectivity of the membrane were successfully improved, and the porosity and pore size distribution of the membrane were optimized, achieving high permeability and selectivity of porous membrane preparation.
Smart Images

Figure CN119793227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous membrane, in particular to a PMIA / F127 / TA porous membrane and a preparation method thereof, and belongs to the technical field of novel high-permeability porous membranes. Background Art
[0002] Porous membranes have been widely used in water treatment technologies such as wastewater reuse, drinking water purification and seawater desalination. Membrane filtration is an efficient and environmentally friendly separation process with very simple operation, so it is often used in water purification treatment with high-end requirements. High-efficiency filtration operations in the industrial field require membrane materials with high flux, effective solute rejection and excellent antifouling properties to meet the needs of more economical and efficient water treatment. The pore structure and surface properties of the membrane materials largely determine the above characteristics. Studies have shown that increasing the surface hydrophilicity of membrane materials can improve their wettability and antifouling properties, and increasing the porosity of membranes with molecular sieving properties can effectively improve the permeability of water. Generally, the porosity of a membrane usually determines its permeability, while the pore size determines its selectivity, so high permeability and selectivity require high porosity and appropriate pore size distribution. In the membrane development process, phase separation of polymer solutions can control the pore size and shape to meet different application requirements.
[0003] A lot of research has been done in the prior art to explore several methods for manipulating membrane porosity. Initially, researchers found that the membrane surface porosity and pore size can be increased by increasing solvent and non-solvent affinity, reducing polymer mass content and increasing phase separation temperature. The adjustment of membrane surface pore parameters usually uses pore formers and additives in the casting solution. As the research progresses, it is found that pore formers, such as hydrophilic polymers and amphiphilic block polymers, have different effects on surface porosity and pore size. Specifically, compared with hydrophilic polymers, amphiphilic block polymers produce higher surface porosity and larger pore size.
[0004] Poly(m-phenylene isophthalamide) (PMIA) is a polymer with remarkable characteristics. Compared with traditional membrane materials such as polysulfone (PSF) and polyethersulfone (PES), PMIA exhibits excellent performance due to its unique structure (connected by alternating benzene rings and amide groups in the backbone chain, polar amide groups forming a hydrogen bond network to enhance the intermolecular force, and benzene rings and amide groups can form a conjugated system), including excellent mechanical strength, good physical and chemical stability and hydrophilicity, etc. Therefore, it is widely used in many fields, including but not limited to space suits, flame retardants and thin films. This material has great application potential and is expected to become a preferred material for membrane manufacturing. In order to further optimize the performance of PMIA membranes, the most common strategy to increase the surface porosity is to increase the exchange rate of solvents and non-solvents, but this will lead to an increase in the pore size of the membrane surface.
[0005] In view of this, it is necessary to conduct in-depth research on the preparation method of high-permeability and high-porosity PMIA polymer membranes to obtain porous membranes with ideal pores and performance for further promotion and application. Summary of the invention
[0006] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a PMIA / F127 / TA porous membrane and a preparation method thereof, wherein the prepared membrane surface presents a uniform, smooth and porous structure, and the interior also has a rich and consistent pore structure, thereby improving the selectivity and permeability of the membrane.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention first discloses a PMIA / F127 / TA porous membrane, which uses PMIA polymer as the main matrix for membrane preparation, uses Pluronic F127 as an additive, and places the membrane in a TA coagulation bath and is prepared using the NIPS method. The membrane surface presents a uniform, smooth and porous structure.
[0009] Preferably, the cross section of the porous membrane has a characteristic asymmetric structure, including a tight epidermis layer on the upper surface, a transition sublayer with finger-like pores, and a supporting bottom layer containing a large number of cellular pores. More preferably, the permeation flux of the porous membrane is as high as 1073.70±77.85L·m-2·h-1. In the present invention, a porous membrane with more surface openings and internal pore structures is prepared by forced segregation technology, thereby obtaining a higher flux.
[0010] The present invention also discloses a method for preparing a PMIA / F127 / TA porous membrane as described above, comprising the following steps:
[0011] S1. Dry PMIA in an oven, mix lithium chloride and DMAc as a composite solvent system, stir and dissolve at 25°C to form a uniform solution;
[0012] S2. Add a certain amount of Pluronic F127 to the solution and stir continuously until Pluronic F127 is completely dissolved to form a uniform solution;
[0013] S3, adding the dried PMIA fiber to the mixture solution, placing it in an oven at 60-100° C., and continuously stirring the polymer solution to accelerate dissolution and ensure uniformity;
[0014] S4, cooling the polymer solution at 25°C, coating it on a glass plate with a non-woven fabric support substrate attached thereto, and controlling the thickness to be 100 to 180 μm;
[0015] S5. In order to obtain the best open porosity on the membrane surface, the glass plate coated with the primary polymer film is quickly immersed in a TA coagulation bath at 25°C. After immersion for 10 to 60 minutes, the TA solution is carefully removed from the glass plate.
[0016] S6. Clean the membrane surface with deionized water and then immerse it in a NaOH solution (pH=12) for 6 to 12 hours to effectively dissolve the TA on the membrane.
[0017] S7. Prepare the target product PMIA / F127 / TA porous membrane and store it in deionized water for later use.
[0018] It should be noted that the solvent used to dissolve the PMIA polymer here is a composite solvent of DMAc and lithium chloride. This is because the polarity of DMAc alone is not enough to dissolve the PMIA polymer. When lithium chloride is added to the DMAc solvent, + and DMAc to form an interactive solid complex using Li + The carbonyl coordination bond between PMIA and Cl - The hydrogen bonds between PMIA and DMAc can effectively dissolve PMIA by building amine groups.
[0019] Preferably, in the aforementioned composite solvent, the added mass percentage of lithium chloride is 4%.
[0020] More preferably, in the aforementioned step S1, the PMIA fiber is placed in an oven at 90° C. for drying for at least 3 hours.
[0021] More preferably, in the aforementioned step S2, the mass percentage of Pluronic F127 in the solution is 0-2.5%.
[0022] More preferably, in the aforementioned step S5, the mass percentage of TA in the coagulation bath is 1.0-3.0%.
[0023] The present invention is beneficial in that:
[0024] (1) The present invention adopts a method combining NIPS and surface forced segregation process to prepare a porous membrane, successfully segregating Pluronic F127 more into the surface pore structure and internal pore structure of PMIA membrane, and the membrane presents a typical asymmetric porous structure. With the increase of the amount of Pluronic F127 added, the finger-like sublayer of the membrane gradually transforms into a network pore structure composed of connected macropores. Due to the surface forced segregation effect brought by TA, the roughness of the membrane increases, the hydrophilicity improves, the average pore size shows a moderate downward trend, and the porosity shows an upward trend, thereby increasing the permeability of the membrane.
[0025] (2) Tannic acid TA is used as a coagulation bath additive. It is rich in phenolic hydroxyl groups and can interact with the material through hydrogen bonds. It can modify the surface and internal pore structure of the polymer membrane. After being treated with 2.0 wt.% TA in the coagulation bath, the membrane flux is as high as 1000 L·m -2 ·h -1 As described above, the present invention provides strong theoretical support and guidance for the formulation, design and manufacturing process of PMIA polymer membranes, and is capable of producing porous membranes with ideal pore structures and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The schematic diagram of the preparation of PMIA / F127 / TA membrane of the present invention;
[0027] Figure 2 FTIR graph of the PMIA / F127 / TA film of the present invention;
[0028] Figure 3 This is a surface SEM structure diagram of the PMIA / F127 / TA film of the present invention;
[0029] Figure 4 is a cross-sectional SEM structure diagram of the PMIA / F127 / TA film of the present invention;
[0030] Figure 5 is an AFM image of the PMIA / F127 / TA film of the present invention;
[0031] Figure 6 This is a diagram showing the water contact angle measurement results of the PMIA / F127 / TA film of the present invention;
[0032] Figure 7 Nano-CT pore structure diagram and porosity data of PMIA / F127 / TA membrane of the present invention;
[0033] Figure 8 Nano-CT structural diagrams of different cross sections of the PMIA / F127 / TA membrane of the present invention;
[0034] Fig. 9 is a cross-sectional nano-CT structure diagram of the PMIA / F127 / TA membrane of the present invention;
[0035] Fig.10 is a pore size distribution diagram of the PMIA / F127 / TA membrane of the present invention;
[0036] Fig.11 This is a graph showing the overall porosity test results of the PMIA / F127 / TA membrane of the present invention;
[0037] Fig.12The pure water flux test result diagram of the PMIA / F127 / TA membrane of the present invention, wherein (a) is the membrane flux change when deionized water and TA are used as the coagulation bath respectively at different Pluronic F127 addition contents; (b) is the membrane flux change when different TA concentrations are used as the coagulation bath; (c) is the membrane flux change at different Pluronic F127 addition contents when TA is used as the coagulation bath. DETAILED DESCRIPTION
[0038] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] Unless otherwise specified in the present invention, all raw materials used are commercially available, and preferred commercial sources are shown in Table 1 below:
[0040]
[0041] Table 1 Preferred commercial sources of each raw material
[0042] Figure 1 The figure shows a schematic diagram of the process of preparing PMIA / F127 / TA membrane by the NIPS method of the present invention. The specific preparation steps are as follows:
[0043] First, PMIA fibers were dried in an oven at 90°C for at least 3 hours. Lithium chloride and DMAc were precisely mixed and dissolved under stirring at 25°C to form a uniform solution.
[0044] Then, a certain amount of Pluronic F127 was added to the solution, and the solution was stirred continuously until the Pluronic F127 was completely dissolved.
[0045] Next, the dried PMIA fibers were added to the mixture solution and placed in an oven at 90°C. It should be noted that the solvent used to dissolve the PMIA polymer here is a mixed solution of DMAc and lithium chloride, because the polarity of DMAc alone is not enough to dissolve the PMIA polymer. When lithium chloride is added to the DMAc solvent, the PMIA polymer will + and DMAc to form an interactive complex, utilizing Li + The carbonyl coordination bond between PMIA and Cl - The hydrogen bond between PMIA and DMAc can effectively dissolve PMIA.
[0046] The polymer solution was continuously stirred to accelerate dissolution and ensure uniformity. The polymer solution was then cooled at room temperature at 25°C and coated on a glass plate with a non-woven fabric support substrate attached thereto, with a thickness of about 150 μm.
[0047] Next, in order to obtain the best segregation of F127 on the membrane surface, the glass plate coated with the liquid film was quickly immersed in a TA coagulation bath at 25°C, where the TA concentrations were 1.0, 1.5, 2.0 and 3.0 wt.%. After soaking for 10 minutes, the TA solution was carefully removed from the glass plate. Then, the membrane surface was cleaned with deionized water and immersed in a NaOH solution (pH = 12) for 8 hours to effectively dissolve the TA on the membrane. Finally, the prepared membrane was immersed in deionized water for testing and characterization.
[0048] The preparation steps of Examples 1 to 8 are basically the same as above, the main difference being the raw materials and amounts used in each example (see Table 2 for details).
[0049]
[0050]
[0051] Table 2 Membrane codes and corresponding component ratios of Examples 1 to 8
[0052] Structural characterization and performance analysis
[0053] (1) Surface chemical structure of the membrane - FTIR infrared detection
[0054] The surface functional groups of PMIA / F127 / TA membranes were analyzed by infrared spectrometer FTIR (VERTEX 80V, Bruker, Germany). During the test, each sample was completely dried before being attached to the infrared test platform. The scanning spectrum range was 500-4000 cm -1 .
[0055] The surface chemical properties of the membrane were characterized by FTIR. Figure 2 As shown, the membrane is at 3283cm -1 There is a broad absorption band near 1535cm, indicating the stretching vibration of the NH bond in the PMIA structure. -1 The absorption vibration nearby is attributed to the stretching vibration of the CN bond, which is another prominent peak in the PMIA structure. -1 The peaks observed in the range are related to the distortion vibrations of the carbon-hydrogen (CH) bonds in PMIA. The absorption intensity of these peaks remained consistent regardless of the concentration of Pluronic F127. This finding suggests that the prepared PMIA / F127 / TA membrane retains the beneficial chemical structure of the PMIA material, allowing it to exhibit the ideal physical and chemical properties of PMIA polymers when used as membranes.
[0056] 2884cm -1The peak near 2884cm is due to the stretching vibration of the CH group in Pluronic F127. -1 The intensity of the absorption band of M1-M5 films increased slightly. -1 An obvious peak appears on the left and right, indicating that the CO functional group of Pluronic F127 undergoes stretching vibration. It can be seen that increasing the amount of Pluronic F127 in the casting solution can enhance the absorption band of CO stretching vibration.
[0057] The above test results show that Pluronic F127 has completely entered the PMIA matrix.
[0058] (2) Membrane microstructure - SEM characterization
[0059] To carefully evaluate the effect of Pluronic F127 on the development of membrane structure, scanning electron microscopy was used to characterize the membrane morphology and structure. Figure 3 The surface microstructure of the prepared membranes is shown, and all the prepared membranes exhibit a uniform, smooth and porous surface. When the concentration of Pluronic F127 in the casting solution increases, the number and permeability of the surface macropores also increase, and the changes in pore size will be verified by subsequent pore size distribution analysis.
[0060] According to the characterization results, Pluronic F127 can be used as a pore inducer and modifier to effectively increase the average pore size and surface porosity of the membrane. This is mainly because the hydrophilic PEO segments on the Pluronic F127 chain can segregate into the coagulation bath, which helps to form a large number of pores and improve the overall porosity. In addition, the SEM image shows the presence of fibrous particles on the M4 membrane. As the concentration increases, the incompatibility between Pluronic F127 and PMIA leads to the observed fibrous behavior. Simply put, due to the presence of Pluronic F127 in the casting solution, the membrane structure will undergo slight changes. Therefore, the addition of amphiphilic Pluronic F127 may disrupt the interaction between the solvent, inorganic salt and polymer, leading to the formation of the above-mentioned fibrous material.
[0061] Figure 4The cross-sectional morphology of PMIA / F127 / TA membrane. From the cross-sectional morphology, it can be seen that the membrane has a typical asymmetric structure, including a tight epidermis on the upper surface, a transition sublayer with finger-like pores, and a supporting bottom layer containing a large number of cellular pores. One of the main reasons for the formation of this special structure is that during the NIPS process, due to the strong attraction between the non-solvent and the solvent, an instantaneous phase separation occurs, forming a porous cross-sectional structure with multiple pores. In addition, with the increase of Pluronic F127 content, the cross-sectional area of the membrane gradually changes from a finger-like sublayer to a macropore, becoming irregular and curved, and the connectivity of the macropores is enhanced. This is because the phase separation rate caused by the self-assembly of the amphiphilic block copolymer increases, which increases the rate at which the gel bath immerses into the polymer body, leading to the formation of a porous structure. In addition, the introduction of TA solution as a forced segregation agent further enhances the segregation of the hydrophilic amphiphilic polymer Pluronic F127 on the membrane surface and internal pore structure, further promoting the improvement of the membrane porosity, and then improving the permeability of the membrane. The permeability of the membrane will be verified by subsequent permeation flux tests.
[0062] The connectivity between the porous structures of the membrane of the present invention is enhanced. Thanks to the segregation effect of Pluronic F127 and the forced segregation effect brought about by the introduction of TA, the development of the pore structure effectively improves the permeability of the membrane. As the concentration of Pluronic F127 increases, the membrane thickness gradually increases, which is mainly due to the addition of the amphiphilic block copolymer greatly increasing the viscosity of the casting polymer solution, thereby increasing the thickness of the membrane. The specific membrane thickness measured is shown in Table 3.
[0063] Serial number Pluronic F127 content (wt.%) Film thickness(μm) Example 1 0 164.4±5.59 Example 2 1 176.6±5.27 Example 3 1.5 179.4±7.33 Example 4 2 181.0±4.30 Example 5 2.5 186.2±0.84
[0064] Table 3 Thickness of PMIA / F127 / TA film
[0065] (3) Surface morphology and properties of the membrane
[0066] The topological structure of the membrane surface was characterized and evaluated by atomic force microscopy (AFM) (Dimension FastScan, Bruker, Germany). Figure 5 A three-dimensional atomic force microscopy image of the film surface is shown, and the corresponding roughness values of the film surface are listed in Table 4 below.
[0067] Film No. <![CDATA[R a (nm)]]> <![CDATA[R max (nm)]]> <![CDATA[R q (nm)]]> M1 11.77±0.12 125.67±19.73 15.03±0.47 M2 13.70±0.36 130.33±9.61 17.47±0.65 M3 16.10±0.60 141.67±11.72 20.03±0.85 M4 17.97±2.66 181.00±56.72 22.93±2.48 M5 21.03±3.12 169.00±8.50 26.20±3.24
[0068] Table 4 Surface roughness values of PMIA / F127 / TA films
[0069] The results show that in the presence of TA as a forced surface segregation coagulation bath additive, the surface roughness of the membrane increases with increasing concentration of Pluronic F127, from 11.77 ± 0.12 nm to 21.03 ± 3.12 nm. This observation is consistent with Figure 3 The results of SEM are consistent with those shown in Figure 2. After analysis, we believe that the increase in roughness can be attributed to the following factors: (1) When Pluronic F127 is used as a pore-forming modifier, it may greatly increase the size and porosity of the membrane, thereby increasing its roughness; (2) Pluronic F127 will undergo surface segregation during the NIPS process. Due to the low interfacial energy between water molecules and hydrophilic blocky PEO, the hydrophilic PEO segments migrate to the overlap between the membrane surface and the inner pore wall, thereby increasing the surface roughness of the membrane; (3) When TA is used as a coagulation bath, it further promotes the segregation of Pluronic F127, especially the subsequent NaOH post-treatment process, which further improves the surface pore structure of the membrane; In addition, the increase of Pluronic F127 in the casting solution may also lead to an increase in membrane roughness, which may be due to the formation of a fibrous structure, such as Figure 3 As shown in the SEM surface image.
[0070] The hydrophilicity of the membrane surface is crucial to its anti-fouling ability, so the water contact method was further used to study the changes in the hydrophilicity of the membrane. Figure 6 As shown in the figure, the water contact angle of the M1 film is 70.0±1.06°, which has a certain hydrophilicity. This is mainly due to the amino groups contained in the PMIA polymer itself and the hydrogen bonding force between the PMIA polymer molecular chains, which provides a certain hydrophilicity for the PMIA matrix. When the content of Pluronic F127 increases to 2.5wt.%, the water contact angle decreases from 70.0±1.06° to 60.9±1.56°, and the membrane surface shows a more hydrophilic trend. This may be because during the diffusion of NIPS, TA is introduced as a coagulation bath, and the hydrophilic segments of Pluronic F127 itself are more segregated to the surface of the membrane, thereby increasing the hydrophilicity of the membrane.
[0071] The above analysis results show that the addition of Pluronic F127 copolymer, TA as a coagulation bath, and NaOH post-treatment can significantly improve the hydrophilicity of the membrane material.
[0072] (4) Nano-CT structure of PMIA / F127 / TA membrane
[0073] Nano-CT is a technology that creates high-resolution three-dimensional (3D) images of materials at the nanometer scale, providing detailed views of objects millions of times smaller than a millimeter and is used to evaluate structural features on the surface of membranes and within them with very high accuracy.
[0074] Figure 7 Nano-CT pore structure and porosity data of PMIA / F127 / TA membrane. Figure 8 Nano-CT structure diagrams of different cross sections of PMIA / F127 / TA membranes. Fig. 9 The cross-sectional nano-CT structures of PMIA / F127 / TA membranes clearly show that the porosity on the surface of the M4 membrane (Pluronic F127 with a mass concentration of 2%) increased from 82.00% to 85.71% compared with that of the M1 membrane (without Pluronic F127). This is due to the presence of Pluronic F127 as a pore generator and the fact that TA as a coagulation bath additive, together with the NaOH post-treatment, enhances the development trend of the pore structure.
[0075] The study also shows that the TA concentration in the coagulation bath also has an important influence on the porosity of the membrane. In 1wt.% (M6), 2wt.% (M4) and 3wt.% (M8), the porosity of the membrane increased accordingly from 84.89% to 85.71%, and finally significantly increased to 90.09%. This shows that the introduction of TA, together with the NaOH post-treatment process, can effectively increase the segregation rate of Pluronic F127 during the phase transformation process through forced segregation. At the same time, the TA etched away by the NaOH post-treatment also contributes greatly to the improvement of the membrane porosity.
[0076] The pore structure distribution characteristics of the membrane are crucial to the membrane separation efficiency. Fig.10 The pore size distribution of the PMIA / F127 / TA membrane is shown. When the amount of Pluronic F127 increases, the average size of the membrane pores increases first and then decreases. Overall, the pore size of the membrane decreases from 0.25±0.02μm to 0.22±0.03μm without addition and with high concentration addition, showing a moderate downward trend. It can be seen that the PMIA / F127 / TA membrane constructed by the preparation method of the present invention has a consistent pore structure, which helps to improve the selectivity and permeability of the membrane.
[0077] Furthermore, the overall porosity of the membrane was tested using the “dry-wet weight method”. The test results are as follows: Fig.11As shown in the figure, with the increase of Pluronic F127 dosage, the porosity of the membrane increased from 59.84±4.23% to 62.44±1.13%. Pluronic F127 can be used as a surface segregation agent to improve the affinity between the membrane surface and water molecules through the surface segregation process. In the whole NIPS method, the membrane matrix has the ability to attract more water molecules, resulting in the expansion of the membrane pores. This expansion leads to an increase in the size and permeability of the membrane pores. At the same time, the introduction of TA as a coagulation bath component improves the segregation efficiency, and the post-etching treatment of NaOH further improves the pore structure. In addition, micelles are formed in the casting solution due to the self-assembly of the block copolymer, which affects the affinity between the solvent and the block copolymer, resulting in the formation of more pore structures during the separation process. In summary, the addition of Pluronic F127, the use of TA as a coagulation bath component, and the post-treatment etching treatment all bring synergistic gain effects to the development of the membrane porous structure.
[0078] (6) Filtration performance of PMIA / F127 / TA membrane
[0079] The separation and permeability of the membrane are the key properties of the membrane. Therefore, the present invention measured the changes in pure water flux of various PMIA / F127 / TA membranes under different Pluronic F127 additive contents, different coagulation bath types, and different coagulation bath compositions. The results are as follows: Fig.12 Shown are: (a) the change in membrane flux when deionized water and TA are used as coagulation baths at different Pluronic F127 addition contents; (b) the change in membrane flux when different TA concentrations are used as coagulation baths; (c) the change in membrane flux when TA is used as coagulation bath at different Pluronic F127 addition contents.
[0080] from Fig.12 As can be seen from (a), with the increase of Pluronic F127 content, the membrane flux using water and TA as gel bath gradually increased, but the membrane permeation flux of adding TA as coagulation bath increased more, indicating that the introduction of TA effectively promoted the formation and development of membrane pore structure, thereby improving the permeability performance of the membrane. Fig.12(b) The effect of different TA concentrations in the coagulation bath on the membrane flux was investigated. It can be seen from the figure that as the TA concentration increased from 1% to 2%, the permeability of the membrane was significantly improved. This was mainly due to the fact that the introduction of TA increased the surface segregation of F127 in the membrane, promoted the phase separation rate, and increased the number of membrane openings. When 3% TA was introduced into the coagulation bath, it was found that the membrane flux decreased compared with the concentration of 2%. This was mainly due to the fact that the introduction of too much TA increased the viscosity of the coagulation bath, which to a certain extent limited the phase separation rate, thereby affecting the film formation rate and the growth and development rate of the pores, resulting in a decrease in the flux. Despite this, the increase in membrane flux produced by 3% TA was still higher than the membrane formation flux at a TA concentration of 1.5%.
[0081] When the weight percentage of Pluronic F127 increased to 2.0%, the pure water flux of PMIA / F127 / TA membrane increased from 586.20±38.63 L·m -2 ·h -1 Increased to 1073.70±77.85L·m -2 ·h -1 This is mainly due to the fact that the change in pore structure has a significant impact on the membrane water flux, and the high concentration of Pluronic F127 added will lead to an increase in the porosity and pore size of the membrane. Therefore, the resistance of water molecules flowing through the membrane pores is reduced, allowing a large number of water molecules to enter the membrane, that is, the water permeability of the membrane is improved. In addition, adding Pluronic F127 to the membrane can also enhance the hydrophilicity of the membrane, while enabling the PEO segments to attract more water molecules and retain them in the membrane matrix, greatly improving the permeability of the membrane.
[0082] In the present invention, the permeability is enhanced by using the Pluronic F127 additive, and TA promotes the phase separation rate by forced segregation to increase the number of pores on the membrane surface and the internal structure of the membrane and the characteristics of the pore structure, which can promote the segregation of Pluronic F127, thereby increasing the phase conversion rate of the film forming process, promoting the improvement of the membrane porosity, and improving the hydrophilicity of the membrane. The superposition of the above beneficial effects further improves the membrane flux. The preparation method of the present invention is expected to save a lot of energy in membrane applications and greatly reduce the investment cost and application cost of the membrane.
[0083] In summary, the present invention adopts a method combining NIPS and surface forced segregation process to prepare a porous membrane, successfully segregating Pluronic F127 more into the surface pore structure and internal pore structure of the PMIA membrane, and the membrane presents a typical asymmetric porous structure. In the case of TA as a coagulation bath additive, with the increase of the amount of Pluronic F127 added, the finger-like sublayer of the membrane gradually transforms into a network pore structure composed of connected macropores. Due to the forced segregation effect brought by TA, the roughness of the membrane increases, the hydrophilicity is improved, the pore structure is developed, and the average pore size increases first and then decreases with the increase of the amount of Pluronic F127 added. It shows a moderate downward trend in the case of no addition and high concentration addition, and the porosity shows an upward trend, thereby increasing the permeability of the membrane.
[0084] Furthermore, after treatment in a 2.0 wt. % TA bath, the membrane flux reached 1073.70 ± 77.85 L·m -2 ·h -1 The present invention provides strong theoretical support and guidance for the formulation, design and manufacturing process of PMIA polymer membranes, and can produce porous membranes with ideal pore structures and properties.
[0085] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A PMIA / F127 / TA porous membrane, characterized in that: The PMIA polymer is used as the main membrane matrix, Pluronic F127 is used as an additive, and the membrane is placed in a TA coagulation bath and prepared by a NIPS method. The membrane surface presents a uniform, smooth and porous structure.
2. A PMIA / F127 / TA porous membrane according to claim 1, characterized in that: The cross section of the porous membrane has a typical asymmetric structure, including a tight skin layer on the upper surface, a transition sublayer with finger-like pores, and a supporting bottom layer containing a large number of cellular cavities.
3. A PMIA / F127 / TA porous membrane according to claim 1, characterized in that: The permeation flux of the porous membrane is as high as 1073.70±77.85 L·m -2 ·h -1 .
4. The method for preparing a PMIA / F127 / TA porous membrane according to claim 1, characterized in that: The steps include: S1. Dry PMIA in an oven, mix lithium chloride and DMAc as a composite solvent system, add LiCl at a ratio of 4%, and stir and dissolve at 25°C to form a uniform solution; S2. Add a certain amount of Pluronic F127 to the solution and stir continuously until Pluronic F127 is completely dissolved to form a uniform mixture solution; S3, adding the dried PMIA fiber to the mixture solution, placing it in an oven at 60-100° C., and continuously stirring to form a polymer solution to accelerate dissolution and ensure uniformity; S4, cooling the polymer solution at 25°C, coating it on a glass plate with a non-woven fabric support substrate attached thereto, and controlling the thickness to be 100 to 180 μm; S5, quickly immersing the glass plate coated with the primary polymer film into a coagulation bath containing TA at 25° C., and after soaking for 10 to 60 minutes, carefully removing the TA solution from the glass plate; S6. Clean the membrane surface with deionized water and then immerse it in NaOH solution for 6 to 12 hours to effectively dissolve the TA on the membrane. S7. Prepare the target product PMIA / F127 / TA porous membrane and store it in deionized water for later use.
5. The method for preparing a PMIA / F127 / TA porous membrane according to claim 4, characterized in that: In the step S1, the PMIA fiber is placed in an oven at 90° C. for drying for at least 3 hours.
6. The method for preparing a PMIA / F127 / TA porous membrane according to claim 4, characterized in that: In the step S1, the mass percentage of lithium chloride added in the composite solvent composed of lithium chloride and DMAc is 4%.
7. The method for preparing a PMIA / F127 / TA porous membrane according to claim 4, characterized in that: In the step S2, the mass percentage of Pluronic F127 in the solution is 0-2.5%.
8. The method for preparing a PMIA / F127 / TA porous membrane according to claim 4, characterized in that: In the step S5, the mass percentage of TA in the coagulation bath is 1.0-3.0%.
Citation Information
Patent Citations
Preparation method of zero-flux attenuation chemical heterogeneous hydrogel ultrafiltration membrane
CN110548420A
Modified polyisophthaloyl metaphenylene diamine ultrafiltration membrane as well as preparation method and application thereof
CN113750804A
Capillary force induced ultra-low pressure separation membrane constructed based on bionic technology and preparation method and application of capillary force induced ultra-low pressure separation membrane
CN115920680A